Answer:
Refer below for the explanation.
Step-by-step explanation:
As per the question we are asked to combine f(n) = 11 and g(n) = −2(n − 1), both of them to create arithmetic sequence and solve for 31st term.
So first we are about to solve and combine both of the equation which becomes ,
Fn = 11 -2(n-1)
Fn=11-2(n-1)
F31=-49
Fn=11-2(n-1)
F31=-51
Fn=11+2(n-1)
F31=71
Fn=11+2(n-1)
F31=73
To create an arithmetic sequence using the given functions, we add the functions together and substitute the desired term. The 31st term of the arithmetic sequence is -49.
To combine the functions f(n) = 11 and g(n) = -2(n - 1) into an arithmetic sequence, we need to find the common difference between the terms. The common difference between the terms in an arithmetic sequence is obtained by subtracting one term from the previous term. In this case, the common difference is g(n). So, the arithmetic sequence can be expressed as an = f(n) + g(n).
For the 31st term, we substitute n = 31 into the equation and calculate:
a31 = f(31) + g(31)
a31 = 11 + [-2(31 - 1)]
a31 = 11 + [-2(30)]
a31 = 11 + [-60]
a31 = -49
Therefore, the 31st term of the arithmetic sequence an is -49.
#SPJ12
B earth rotates on its axis
C earth Axis is titled
D the moon revolves around earth
Answer:
why are there season
A earth revolves around the sun
B earth rotates on its axis
C earth Axis is titled
D the moon revolves around earth
Step-by-step explanation:
The stations are due to the inclination of the axis of rotation of the Earth with respect to the plane of its orbit with respect to the sun, which means that some regions receive different amounts of sunlight depending on the time of year.
The Earth rotates around its axis, this rotating movement is called rotation.
The answer is: C. The axis of the earth is tilted.
Answer:
lol just use the same formula i put on the other one. Yeesh, girl
Step-by-step explanation:
Answer:
The answer is 0.2
Step-by-step example
First multiply two and sixty which equals 120,then multiply ten and sixty which equals six hundred then divide it by eachother which equals zero point two.
Answer:
g = 7 + 9e - 3e /4
Step-by-step explanation:
3e + 4g = 7 + 9e
Subtract 3e from both sides to eliminate 3e on the left side
3e - 3e + 4g = 7 + 9e - 3e
4g = 7 + 9e - 3e
Divide both sides by 4 to isolate g
4g/4 = 7 + 9e - 3e /4
g = 7 + 9e - 3e /4
Answer:
g=(7+9e-3e)/4
Step-by-step explanation:
3e+4g=7+9e
4g=7+9e-3e
g=(7+9e-3e)/4